A conceptual model for generating and validating in-session clinical judgments - Jacinto, S. B.; Lewis, C. C.; Braga, J. N.; Scott, K. (Psychotherapy Research, 2018)
Objective: Little attention has been paid to the nuanced and complex decisions made in the clinical session context and how these decisions influence therapy effectiveness. Despite decades of research on the dual-processing systems, it remains unclear when and how intuitive and analytical reasoning influence the direction of the clinical session. Method: This paper puts forth a testable conceptual model, guided by an interdisciplinary integration of the literature, that posits that the clinical session context moderates the use of intuitive versus analytical reasoning. Results: A synthesis of studies examining professional best practices in clinical decision-making, empirical evidence from clinical judgment research, and the application of decision science theories indicate that intuitive and analytical reasoning may have profoundly different impacts on clinical practice and outcomes. Conclusions: The proposed model is discussed with respect to its implications for clinical practice and future research.